Rapid identification of CMV-specific TCRs via reverse TCR cloning system based on bulk TCR repertoire data - Hong, Cheol-Hwa; Pyo, Hong-Seon; Baek, In-Cheol; Kim, Tai-Gyu (Frontiers in Immunology, 2022)
Advances in next-generation sequencing (NGS) have improved the resolution of TCR repertoire analysis and recent single-cell sequencing have made it possible to obtain information about TCR pairs. In our previous study, CMV pp65-specific T cell response restricted by single HLA class I allotype was observed in an individual. Therefore, to effectively clone an antigen-specific TCR from these T cells, we developed a TCR cloning system that does not require single cell level. First, we established the improved Jurkat reporter cell line which was TCRαβ double knock-out and expressed CD8αβ molecules. Furthermore, functional TCRs were directly obtained by reverse TCR cloning using unique CDR3 specific PCR primers after bulk TCR sequencing of activation marker positive CD8 T cells by NGS. Total 15 TCRα and 14 TCRβ strands were successfully amplified by PCR from cDNA of 4-1BB positive CD8 T cells restricted by HLA-A*02:01, -A*02:06, -B*07:02, and -B*40:06. The panels with combinations of TCRα and TCRβ genes were investigated using Jurkat reporter cell line and artificial APCs. In 2 TCR pairs restricted by HLA-A*02:01, 1 TCR pair by HLA-A*02:06, 4 TCR pairs by HLA-B*07:02, and 1 TCR pair by HLA–B*40:06, their specificity and affinity were confirmed. The TCR pair of A*02:01/1-1 showed alloreactivity to HLA-A*02:06. The 1 TCR pair showed a higher response to the naturally processed antigen than that of the peptide pool. This reverse TCR cloning system will not only provide functional information to TCR repertoire analysis by NGS, but also help in the development of TCR-T therapy.